Association between FSH, E1, and E2 levels in urine and serum in premenopausal and postmenopausal women - Onizuka, Yoko; Nagai, Kazue; Ideno, Yuki; Kitahara, Yoshikazu; Iwase, Akira; Yasui, Toshiyuki; Nakajima-Shimada, Junko; Hayashi, Kunihiko (Clinical biochemistry, 2019)
We aimed to establish correlations for the levels of follicle-stimulating hormone (FSH), estrone (E1) and estradiol (E2) between urine and serum in premenopausal and postmenopausal women using immunoassays. In this study of 92 women (61 postmenopausal, 31 premenopausal), both urine and blood specimens were collected on the same day and stored at 4 °C for analysis by chemiluminescent immunoassay, radioimmunoassay and/or electrochemiluminescent immunoassay. There were correlations in the levels of FSH, E1 and E2 between urine and serum in both postmenopausal (r = 0.96 for FSH, r = 0.91 for E1, r = 0.80 for E2) and premenopausal (r = 0.98 for FSH, r = 0.92 for E1, r = 0.90 for E2) women. It is indicated that the correlations were stronger in the premenopausal group compared with the postmenopausal group, especially for FSH. The levels of FSH, E1 and E2 in urine correlated with those in the serum in premenopausal and postmenopausal women. Urine samples could be used instead of serum samples to measure hormone levels, which would reduce the difficulty of conducting large survey studies. •Urine sampling is less invasive than blood sampling.•Urinary FSH, estrone and estradiol levels correlated with serum levels.•Urine samples to measure sex hormones may ease burden of running large survey studies.